PERAN VISKOSITAS DARAH PADA STROKE ISKEMIK AKUT - Al Rasyid (Neurona Majalah Kedokteran Neuro Sains, 2014)
BLOOD VISCOSITY IS THE RESISTANCE OF BLOOD TO FLOW CAUSED BY FRICTION DUE TO BLOOD MOVEMENT THROUGH THE LAMINA ALONG THE AXIS OF BLOOD VESSELS DUE TO DIFFERENCES IN BLOOD FLOW SPEED BLOOD VISCOSITY VALUE DEPENDS ON HEMORRHEOLOGICAL COMPONENTS AND OTHER FACTORS INCLUDING AGE SMOKING HYPERTENSION DIABETES MELLITUS AND CARDIAC DISEASE BLOOD VISCOSITY PLAYS AN PIVOTAL ROLE IN DETERMINING CEREBRAL BLOOD FLOW IN ACUTE ISCHEMIC STROKE PATIENTS BLOOD HYPERVISCOSITY WHICH CAN REDUCE CEREBRAL BLOOD FLOW INCREASE INFARCT VOLUME AND INCREASE THE OUTCOME SEVERITY IS DETECTED IN MORE THAN 40 PATIENTS WITH ACUTE ISCHEMIC STROKE